Institutional processes in the payment for ecosystem services, Pasto River Watershed - Narváez R., Yesenia Alejandra; Paz A., Wilmer Javier; Guapucal C., Mirian del Rosario; Leonel, Hugo Ferney (Revista de Ciencias Agrícolas, 2016)
Payment for ecosystem services (PES) is the opportunity for an individual or social group to gain benefit from or to conserve the natural environmental offer. This study was conducted in the Pasto River Watershed, where the main ecosystem service is providing water supply to 85% of inhabitants of the city of Pasto, Nariño, making it a strategic ecosystem that requires viable alternatives for its conservation and management. The aim of this study was to evaluate processes related with PES carried out by several institutions, for which we designed a structured interview that was applied to personnel from four institutions and included the following variables: institution, knowledge of the norm, financial resources, technical support, current activities, and possible alternatives for PES. Alternatives for improvement in PES were proposed using the software Decision Explorer 3.3 and with participants from the institutions. We determined that the township of Cabrera is carrying out alternatives such as implementation of agroforestry systems, park ranger families, and acquisition of lands for PES. We concluded that PES in the Pasto River watershed is rudimentary, yet promising; there is little institutional knowledge and processes have focused on buying lands for the conservation of rural and municipal water supply systems.